Problems faced by the rural women beneficiaries in participating shouhardo II program - Nath, TD; Hoque, MJ; Farouque, MG (Progressive Agriculture, 2016)
The main focus of the study was to identify and describe the problems faced by the rural women beneficiaries in participating in SHOUHARDO II program. The study was conducted in Doribhabkhali village of Bhabkhali Union Parisad of Mymensingh Sadar Upazila under Mymensingh district. Data were collected from sixty rural women beneficiaries from 381 beneficiaries using random sampling method in April, 2015. The highest proportion of the rural women beneficiaries (41.7 percent) faced medium problems in participating program, while 33.3 percent of them had low problems. Among nine selected problems religious obstacle got the highest score (TOSS-156) and hence was considered as 1st ranked problem and incompatibility with the participants got the lowest score (TOSS-29) and hence was considered as9th ranked problem. The selected characteristics of the respondents, such as household size showed positive relationship while extension media contact and social mobility showed negative with problem confrontation in participating SHOUHARDO II program. On the basis of probable solutions (correct interpretation of religious issues, increasing duration of training program etc.) made by rural women beneficiaries, necessary steps should be taken to reduce the faced problems. Progressive Agriculture 27 (2): 200-206, 2016